Static Analysis-Based Security Enhancement for Mobile Applications Using Mobile Security Framework (MOBSF) - Nur Izzati, Putri; Kasmawi, Kasmawi (Politeknik Negeri Batam, 2025)
Mobile application security is crucial to protect users’ personal data and maintain trust in the application. Without proper security testing, an app becomes vulnerable to threats such as data theft and cyber attacks. This study aims to identify and fix security vulnerabilities in the XYZ mobile application, a social platform used to report domestic violence and child sexual abuse cases. The analysis was conducted using static analysis with the Mobile Security Framework (MOBSF). The XYZ app was developed using Flutter and falls under the hybrid application category. Since it handles sensitive information from victims and reporters, ensuring its security is essential. The analysis revealed four major vulnerabilities with high risk levels, mainly related to misconfiguration and weak security settings. After addressing these issues, the app’s security score improved from 37/100 (high risk) to 61/100 (low risk). These improvements were implemented in the final development phase before the app was released to users. MOBSF helped developers detect potential vulnerabilities early through static analysis, serving as a security baseline. This approach ensured the app no longer contained risks such as debug certificates, enabled debug mode, or support for outdated Android versions. The findings show that MOBSF-based security analysis is effective in detecting and reducing application security weaknesses, making the XYZ app more secure in protecting user data.